ACSM's complete guide to fitness and health. - Bushman, Barbara, ....- (Champaign : Human Kinetics, 2011)
You know the importance of good health, but how do you achieve it? And how do you maintain it through the years as your body and lifestyle change, introducing obstacles to physical activity and optimal nutrition? In ACSM's Complete Guide to Fitness & Health, you will find the answers and much, much more. The American College of Sports Medicine, the largest and most-respected sport science and medicine organization in the world, has created the ACSM's Complete Guide to Fitness & Health to strip away common fads, myths, and misconceptions and provide you with the latest research, sound advice, and age-specific recommendations that you can trust. You will learn these strategies: > Optimize your weight, improve heart health, and increase aerobic fitness, strength, flexibility, and balance. > Improve your health by managing diabetes, high blood pressure, high cholesterol, arthritis and joint pain, pregnancy, and osteoporosis through exercise and proper nutrition. > Determine your body composition and current cardiorespiratory and muscular fitness levels. > Monitor, evaluate, and adjust your exercise program over time for optimal results. > Introduce exercise, increase physical activity, and improve your diet for more energy and better health (no matter what your age!). Featuring step-by-step instructions and full-color photos for the most effective exercises, sample workouts, practical advice, age-specific physical activity guidelines, and strategies for incorporating exercise into even the busiest of lifestyles
Omslag vermeldt: Physical activity and nutrition guidelines for every age.
Keywords: Fitness; Gezondheid; Voeding en gezondheid